Inclusive pedagogies in mathematics education: Experiential learning for deaf learners in specialized settings - Hatsu , Edo; Boateng , Francis Ohene; Arthur, Yarhands D.; Akosah, Ernest Frimpong (American Journal of STEM Education, 2025)
In this paper, we examined the effects of experiential learning combined with collaborative teaching on the mathematics achievement of deaf learners in specialized classrooms. A quasi-experimental design was employed, comparing pre-test and post-test scores of a control group that received traditional instruction with those of an experimental group taught through experiential learning using collaborative methods. Both groups showed improvement, but the experimental group demonstrated significantly greater gains. Findings confirm the effectiveness of learner-centered approaches in enhancing engagement and understanding among deaf students. The study aligns with global education reform efforts that advocate for inclusive, adaptive teaching practices. It highlights the importance of innovative pedagogies in addressing diverse learner needs and promoting equitable outcomes, particularly in specialized and cross-cultural educational settings.